O desenvolvimento da consciência fonológica no processo de alfabetização - Niedermayer, Luci Piletti (2019)
This work concerns the development of phonological awareness in the process of appropriating the alphabetical writing system. It is based on a research and an investigation about the alphabetization process, its theoretical and methodological presuppositions and as perceptible gaps along the way, do not develop as competences to read, produce, understand, interpret and interact with the text, do use of the Portuguese language in the various social situations. In regard of these reflections and understanding the development of metaphonological skills as a fundamental course for the learning process of the Portuguese language, our research was based on the main objective of evaluating the contributions of a work developed from textual genres to the development of phonological awareness, in alphabetization class. For this, we start with the following research question: did a didactic unit organized around textual genres focusing on grapheophonic relations contribute to the development of phonological awareness in a alphabetization room? The study was constituted in the light of Historical-Cultural Psychology, whose discussions about the development of concepts and about learning were taken as a reference for reflection. It was in the scope of Applied Linguistics, because it problematizes an aspect of the language in use in a school context of teaching, being the research of the qualitative type interpretativist. We developed mediation through a didactic unit based on the approach of the genres of song, poem, tongue-latch, list and speech. The data collection was possible by means field diary and written productions of students from a class of 1st. year of elementary school. As a result of this research process, we maintain the relevance of the work with phonological awareness for a more consistent learning in relation to the knowledge of our language and we understand that such textual genres worked are very productive for the perception and assimilation of the grapophonic relations, with a view to development of reading and writing, in the school alphabetization phase.